"After film club, I actually got better at everything": School engagement and the impact of an after-school film club. (March 2019) - Chapin, Laurie A.; Deans, Carolyn L.; Fabris, Monique A.
Abstract: Early adolescents from culturally diverse backgrounds are at higher risk of school disengagement, especially as they transition to secondary school. Extracurricular activities have potential to build engagement and social skills. This study examines the experiences of students attending a weekly after-school film club where students produce their own short films. Ten students aged 10–14 years participated in semi-structured interviews, analysed to elucidate the personal meaning students ascribed to their experiences. Students reported that film club fostered a desire to learn, a sense of social connection, and autonomy. This experience was related to developing confidence and self-efficacy, group inclusiveness and the ability to recognise different ways of being in differing contexts. These experiences acted as forerunners to positive engagement in the classroom. Positive outcomes potentially included the transfer of skills, improved classroom engagement, greater perspective taking, empathy, and social responsibility. Highlights: Film club students reported positive experiences including self-efficacy, group belonging, and increased confidence. Students said their experiences had impacts on school engagement, like a desire to learn, autonomy, and social skills. Film club was a creative experience and has potential to positively impact students from a diverse range of backgrounds.